Mesenchymal stem cell-derived exosomes for treatment of sepsis - Homma, Kento; Bazhanov, Nikolay; Hashimoto, Kazuki; Shimizu, Masaru; Heathman, Thomas; Hao, Qi; Nawgiri, Ranjana; Muthukumarana, Vidarshi; Lee, Jae Woo; Prough, Donald S.; Enkhbaatar, Perenlei (Frontiers in Immunology, 2023)
Introduction: The pathogenesis of sepsis is an imbalance between pro-inflammatory and anti-inflammatory responses. At the onset of sepsis, the lungs are severely affected, and the injury progresses to acute respiratory distress syndrome (ARDS), with a mortality rate of up to 40%. Currently, there is no effective treatment for sepsis. Cellular therapies using mesenchymal stem cells (MSCs) have been initiated in clinical trials for both ARDS and sepsis based on a wealth of preclinical data. However, there remains concern that MSCs may pose a tumor risk when administered to patients. Recent preclinical studies have demonstrated the beneficial effects of MSC-derived extracellular vesicles (EVs) for the treatment of acute lung injury (ALI) and sepsis. Methods: After recovery of initial surgical preparation, pneumonia/sepsis was induced in 14 adult female sheep by the instillation of Pseudomonas aeruginosa (~1.0×1011 CFU) into the lungs by bronchoscope under anesthesia and analgesia. After the injury, sheep were mechanically ventilated and continuously monitored for 24 h in a conscious state in an ICU setting. After the injury, sheep were randomly allocated into two groups: Control, septic sheep treated with vehicle, n=7; and Treatment, septic sheep treated with MSC-EVs, n=7. MSC-EVs infusions (4ml) were given intravenously one hour after the injury. Results: The infusion of MSCs-EVs was well tolerated without adverse events. PaO2/FiO2 ratio in the treatment group tended to be higher than the control from 6 to 21 h after the lung injury, with no significant differences between the groups. No significant differences were found between the two groups in other pulmonary functions. Although vasopressor requirement in the treatment group tended to be lower than in control, the net fluid balance was similarly increased in both groups as the severity of sepsis progressed. The variables reflecting microvascular hyperpermeability were comparable in both groups. Conclusion: We have previously demonstrated the beneficial effects of bone marrow-derived MSCs (10×106 cells/kg) in the same model of sepsis. However, despite some improvement in pulmonary gas exchange, the present study demonstrated that EVs isolated from the same amount of bone marrow-derived MSCs failed to attenuate the severity of multiorgan dysfunctions.